Differentiation of Effect Across Systemic Literacy Programs in Rwanda, the Philippines, and Senegal. Issue 155 (March 2017) - Christina, Rachel; Vinogradova, Elena
Abstract: In this article, we compare three localized applications (in Rwanda, Senegal, and the Philippines) of a literacy approach for resource‐lean environments and examine the factors influencing its impact in each context, considering dosage, duration, and environment. In Rwanda, a bilingual early grade literacy initiative implemented in partnership with the ministry of education included literacy standards development, training for early grade teachers, materials development, leadership support, and community‐based activities. In the Philippines, a primary grades trilingual curriculum was implemented in close collaboration with the Department of Education to strengthen its literacy component through standards development, teacher and school leader training, materials development, and awareness campaigns. Finally, in Senegal, a program was conducted supporting the YMCA's efforts to improve local educational outcomes by training youth volunteers to mentor students at risk and by engaging families and communities.